Insect meals as emerging protein source in the aquafeed sector: Emphasis on complementary effects to fishmeal, digestibility, carcass characterisation and immunomodulation in aquatic species - Jannathulla, R.; Rajaram, V.; Ambasankar, K.; Sravanthi, O.; Gopikrishna, G.; Dayal, J. S. (Indian Journal of Fisheries, 2022)
Insect meals received great attention in the aquafeed sector during the past decade due to the unsustainable demand for fishmeal. Desirable nutrient content, especially protein with balanced amino acids is of great importance in the use of insect meals as a viable protein source in aquafeeds. Insect meal could complement about 20-75% of dietary fishmeal in various aquatic species. They have better digestibility compared to low-quality fishmeal, oil meals/cakes, fermented plant proteins, feather meal; blood and meat meal and showed equal performance to high-quality fishmeal. Though partial substitution of fishmeal using insect meals could promote the health status, complete substitution resulted in detrimental effects in some aquatic species. This review concludes that insect meals are of great importance as a sustainable protein source and a viable complement to fishmeal in aquafeeds, thereby, helping to reduce the tremendous demand on fishmeal.Keywords: Aquafeed, Carcass characterisation, Fishmeal, Immunomodulatory effect, Insect meal